Silicon-carbon composite material containing covalent organic framework material coating layer and preparation method of silicon-carbon composite material
By constructing a covalent organic frame material cladding layer on the surface of silicon carbon negative electrode material, the problems of electrode powdering and shedding caused by SEI film instability, low Coulomb efficiency for the first time and volume expansion are solved, and the electrochemical performance of lithium-ion batteries is significantly improved.
Patent Information
- Application Number
- CN202411837380.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
AI Technical Summary
Silicon-carbon anode material faces instability of solid electrolyte interface mask (SEI), low first Coulomb efficiency and severe volume expansion in lithium-ion batteries, which limits its large-scale production and application.
Using silicon-carbon composite materials containing a covalent organic frame material cladding layer, the covalent organic frame material cladding layer is constructed on the surface of the silicon-based/porous carbon composite material to prevent direct contact between the electrolyte and the silicon particles, stabilize the SEI film, and enhance the adhesion between the material and the conductive agent through rich active functional groups.
It effectively suppresses the volume expansion of silicon-carbon negative electrode material, stabilizes the SEI film, improves the first Coulomb efficiency, enhances the bonding ability and mechanical properties of the electrode material, and improves the electrochemical performance of lithium-ion batteries.
Smart Images

Figure CN119695101A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a negative electrode material for a lithium ion battery, and in particular to a silicon-carbon composite material containing a covalent organic framework material coating layer and a preparation method thereof. Background Art
[0002] Silicon-carbon anode materials have the advantages of high energy density, long cycle life, and environmental friendliness, and are considered key materials to promote the development of electric vehicles and energy storage. However, silicon-carbon anodes still face many challenges in practical applications, especially the instability of the solid electrolyte interface (SEI), low initial coulombic efficiency, and severe volume expansion leading to electrode pulverization and shedding. These problems have seriously restricted the large-scale production and application of silicon-carbon anodes.
[0003] The instability of the SEI film will lead to the continuous decomposition of the electrolyte, which not only consumes the limited lithium source, but also aggravates the growth of the battery's internal resistance, affecting the battery's cycle efficiency and safety. In addition, the huge volume change of silicon-carbon materials during the charging and discharging process causes the SEI film to frequently rupture and rebuild, further deteriorating battery performance.
[0004] Improving the first coulombic efficiency of silicon-carbon materials directly increases the initial energy output of the battery by reducing irreversible lithium loss, which is crucial to improving the overall energy density of the battery.
[0005] On the other hand, the type and number of functional groups on the surface of silicon-carbon materials directly affect their interaction with the electrolyte and the bonding strength with the current collector. The surface of unmodified silicon-carbon materials often lacks sufficient active sites, making it difficult to form a strong interface bond, resulting in material shedding during the cycle and reduced cycle stability.
[0006] Therefore, developing a new coating modification technology that can effectively improve the stability of the SEI film of silicon-carbon anode, significantly improve the first coulombic efficiency, and enhance the bonding ability of electrode materials by regulating surface functional groups is of great significance for breaking through the existing bottleneck of silicon-carbon anode and improving its cycle stability and practical application value. The present invention aims to provide a new solution for the performance optimization of silicon-carbon anode materials through an innovative coating strategy. Summary of the invention
[0007] The first technical purpose of the present invention is to solve the problems in the background technology and provide a silicon-carbon composite material containing a covalent organic framework material coating layer that effectively inhibits the volume expansion of the silicon-carbon negative electrode material and improves its comprehensive performance.
[0008] The second technical purpose of the present invention is to solve the problems in the background technology and provide a silicon-carbon composite material containing a covalent organic framework material coating layer and a preparation method thereof.
[0009] The first technical purpose of the present invention is achieved through the following technical solutions.
[0010] A silicon-carbon composite material containing a covalent organic framework material coating layer comprises a silicon-based / porous carbon composite material and a coating layer coated on the surface of the silicon-based / porous carbon composite material, wherein the coating layer is a covalent organic framework material, and the covalent organic framework material is a crystalline porous polymer material connected by covalent bonds and synthesized from a first monomer and a second monomer in the presence or absence of a catalyst; the first monomer is one of a boric acid (ester) monomer, a carbonyl monomer, and an oxazine monomer; and the second monomer is one of a phenolic monomer, an amino monomer, and a carbonyl monomer.
[0011] The above-mentioned coating layer is a covalent organic framework material with the following characteristics: first, a protective barrier is constructed on the surface of the silicon particles to effectively isolate the direct contact between the electrolyte and the silicon particles, thereby curbing the continuous decomposition reaction of the electrolyte and stabilizing the SEI film; second, the rich active functional groups can significantly enhance the adhesion between the material and the conductive agent; third, the covalent organic framework material has a regular network structure, which can significantly improve the mechanical properties of the silicon-carbon composite material and effectively inhibit the huge volume expansion of the silicon-carbon negative electrode material during the lithium insertion process.
[0012] Preferably, when the first monomer is a boric acid (ester) monomer, the second monomer is a phenolic monomer, an amino monomer or a carbonyl monomer; when the first monomer is a carbonyl monomer, the second monomer is an amino monomer or a phenolic monomer; when the first monomer is an oxazine monomer, the second monomer is an amino monomer or a carbonyl monomer.
[0013] Preferably, the phenolic monomer is selected from phenolic compounds containing multiple phenolic hydroxyl groups and their aldehyde or amino substituents, such as catechol, resorcinol, hydroquinone, 2,3,6-trimethylphenol, 1,3,5-triformyl phloroglucinol, 2,4,6-trimethylphenol, 2,4,6-triformyl phloroglucinol, 2,2'-biphenol, 4,4'-biphenol, 2,3,4,5,6-pentamethylphenol, 2,4-dimethylphenol, 2,6-dimethylphenol, 4-tert-butylphenol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, etc.
[0014] Preferably, the carbonyl monomer is selected from benzaldehyde derivatives and carboxylic acid compounds containing multiple carbonyl groups, such as terephthalaldehyde, trimesic acid, 2-hydroxy-1,3,5-benzenetricarboxaldehyde, 2,4,6-trihydroxybenzene-1,3,5-tricarboxaldehyde, 2,5-dihydroxyterephthalaldehyde, 2,3,5,6-tetrafluorobenzaldehyde, 2,5-dimethoxyterephthalaldehyde, 2,5-dibromoterephthalaldehyde, 3,4',5-trialdehyde-1,1-biphenyl, 1,3,5-trimethoxy-2,4,6-tricarboxylic acid Benzene, tris(4-formylphenyl)amine, 1,4-dialdehyde-2,5-divinylbenzene, 3,3'-bipyridine-6,6'-dicarboxaldehyde, [2,2']-bithiophene-5,5'-dicarboxaldehyde, 2,4,6-trichlorobenzene-1,3,5-tricarbaldehyde, 1,3,6,8-tetrakis(4-formylphenyl)pyrene, 4'-(hydroxymethyl)-4-biphenylcarboxylate, 2-formyl-1,4-benzenedicarboxylic acid, etc.
[0015] Preferably, the above-mentioned boronic acid (ester) monomer refers to a boronic acid monomer or a boronic acid ester monomer, and the boronic acid (ester) monomer is selected from phenylboronic acid containing multiple boronic acid groups and phenylboronic acid substituted by ethynyl, formyl, amino, nitro or halogen atoms, such as 1,4-phenyldiboronic acid, 2,2'-biphenyldiboronic acid, 4,4'-biphenyldiboronic acid, 3-(methoxycarbonyl)-2-methylphenylboronic acid, 1,2-di(4-borylphenyl)-1,2-diphenylethylene, 5-methoxyformyl-2-methylphenylboronic acid, 3,5-diformylphenylboronic acid, 4-ethynylphenylboronic acid, 3-phenyl-5-pyridineboronic acid ester, 4-boronic acid ester-4',4'-dibutoxytriphenylamine, etc.
[0016] Preferably, the amino monomer is selected from aniline compounds containing multiple amino groups and their derivatives, benzylmethane or aminonaphthalene compounds substituted with multiple aminophenyl groups, such as o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 1,3,5-triaminobenzene, 4,5-dimethoxy-1,2-phenylenediamine, benzidine, 2,5-diaminoterephthalic acid, 4,4'-diaminobiphenyl, 1,3,5-tris(4-aminophenyl)benzene, 4,4',4''-triaminotriphenylmethane, tetrakis(4-aminophenyl)methane, 2,4-diaminobenzenesulfonic acid, diaminoazobenzene, 2,6-diaminoanthraquinone, 5-aminonaphthalene-1,3-disulfonic acid, etc.
[0017] Preferably, the above-mentioned azine monomer is selected from polyazine compounds, compounds containing multiple pyrimidine rings or compounds containing multiple pyridine rings. For example, 4,4'-diamino-2,2'-bipyridine, 6,6'-divinyl-2,2'-bipyridine, 4-ethynyl-2,2'-bipyridine, 2,2'-bipyridine-4-carboxaldehyde, 2,2'-bipyridine-5,5'-dicarboxaldehyde, 2,2'-bipyridine-4-carboxylic acid methyl ester, 2,2-bipyridine-6-carboxylic acid, 2-methoxy-5-methylpyrazine, 4,6-dimethyl-2-aminopyrimidine, 2-ethyl-4,6-dihydroxypyrimidine, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 3,5-diamino-6-(2,4-dichlorophenyl)-1,2,4-triazine, 1,3,5-triazine-2,4,6-tricarboxaldehyde, 2,4,6-tripyrimidinyl triazine, etc.
[0018] Preferably, the catalyst is a Lewis acid selected from one or more of formic acid, acetic acid, trifluoroacetic acid, benzenesulfonic acid, polyphosphoric acid (PPA), benzoic anhydride, acetic anhydride, and toluenesulfonic acid. When there are multiple catalysts, they can be combined in any proportion. The catalyst may be added or not.
[0019] Preferably, the synthesis method of the above-mentioned covalent organic framework material includes solvothermal method, ionothermal method, microwave radiation method, mechanical chemical grinding method, mechanical mixing method and the like.
[0020] The second technical purpose of the present invention is achieved through the following technical solutions.
[0021] A method for preparing a silicon-carbon composite material containing a covalent organic framework material coating layer comprises the following steps: (1) Add the silicon-based / porous carbon composite material into a mixing tank, add the first monomer and mix evenly to obtain a primary mixed material.
[0022] (2) Add the second monomer to the primary mixed material, and mix again with or without a catalyst to obtain a secondary mixed material.
[0023] (3) The secondary mixed material is heated and solidified in a vacuum oven or under the protection of an inert atmosphere to obtain the product.
[0024] Preferably, in step (1), the particle size of the silicon-based / porous carbon composite material is 0.1-80 μm, preferably 1-50 μm, and more preferably 1-20 μm; the mass percentage of silicon is 20%-80%, preferably 30%-70%, and more preferably 40%-60%; the BET multi-point specific surface area is 0.1-500 m2 / g, preferably 0.5-200 m2 / g, and more preferably 0.8-100 m2 / g.
[0025] Preferably, in step (1)-step (2), the particle size of the first monomer is 0.1-200 μm, preferably 1-100 μm, and more preferably 2-50 μm; the particle size of the second monomer is 0.1-200 μm, preferably 1-100 μm, and more preferably 2-50 μm; the molar ratio of the first monomer to the second monomer is 1:0.2-6, preferably 1:0.2-3, and more preferably 1:0.5-3; the ratio of the total mass of the first monomer and the second monomer to the mass of the silicon-based / porous carbon composite material is 0.05%-20%, preferably 0.1%-15%, and more preferably 0.5%-10%.
[0026] Preferably, in step (1), the mixing speed of the primary mixed material is 200-3000 rpm (e.g., 500 rpm, 800 rpm, 1200 rpm, 1500 rpm, 2000 rpm, 3000 rpm, etc.), and the mixing time is 5-180 min (e.g., 5 min, 30 min, 60 min, 90 min, 120 min, 150 min, 180 min, etc.).
[0027] Preferably, in step (2), the mixing speed of the secondary mixed material is 200-3000 rpm (e.g., 500 rpm, 800 rpm, 1200 rpm, 1500 rpm, 2000 rpm, 3000 rpm, etc.), and the mixing time is 5-180 min (e.g., 5 min, 30 min, 60 min, 90 min, 120 min, 150 min, 180 min, etc.).
[0028] Preferably, in step (3), the temperature of the secondary mixture during heating and curing is 60°C-400°C (for example, 60°C, 100°C, 150°C, 200°C, 300°C, 400°C, etc.), and the heating time is 0.5-168h (for example, 0.5h, 1h, 3h, 5h, 8h, 10h, 12h, 48h, 96h, 128h, 168h, etc.).
[0029] In order to further improve the conductivity of the material, a carbonization step (4) may be added after step (3). The carbonization process is as follows: under the protection of an inert gas, the silicon-carbon composite material containing a covalent organic framework material coating layer is heated from room temperature to a carbonization temperature, kept at this temperature for a certain period of time, and then cooled to obtain a carbonized silicon-carbon composite material containing a covalent organic framework material coating layer.
[0030] In step (4), the inert gas is nitrogen or argon, the heating rate is 0.1-50°C / min (for example, 0.1°C / min, 1°C / min, 5°C / min, 10°C / min, 20°C / min, 30°C / min, 50°C / min, etc.); the carbonization temperature is 500-1000°C (for example, 500°C, 600°C), 800°C, 850°C, 900°C, 1000°C, etc.); the carbonization time is 1-12h (for example, 1h, 2h, 5h, 8h, 10h, 12h, etc.).
[0031] A purification step may be added between step (3) and step (4): adding a sufficient amount of organic solvent to the silicon-carbon composite material containing the covalent organic framework material coating layer, stirring thoroughly, removing the solvent after soaking for a period of time, and drying the powder to obtain a purified silicon-carbon composite material containing the covalent organic framework material coating layer. This step may be repeated multiple times depending on the purification effect.
[0032] In the above purification step, the organic solvent used is selected from one or more of ethanol, isopropanol, dimethylformamide (DMF), pentane, hexane, octane, methyl acetate, ethyl acetate, propyl acetate, acetone, etc., and the method for removing the solvent includes precipitation, centrifugation, filtration, etc. The drying is carried out under vacuum or inert atmosphere, the drying temperature is 60°C-300°C (for example, 60°C, 100°C, 150°C, 200°C, 300°C, etc.), and the drying time is 0.5-12h (for example, 0.5h, 1h, 3h, 5h, 8h, 10h, 12h, etc.).
[0033] Compared with the prior art, the present invention has the following advantages: First, a layer of covalent organic framework material coating is formed in situ on the surface of the silicon-carbon material particles, which can effectively isolate the direct contact between the electrolyte and the silicon particles and prevent the continuous decomposition reaction of the electrolyte, thereby stabilizing the SEI film and improving the first coulomb efficiency; secondly, the rich active functional groups can significantly enhance the adhesion between the material and the conductive agent; in addition, the covalent organic framework material has a regular network structure, which can significantly improve the mechanical properties of the silicon-carbon composite material, effectively inhibit the huge volume expansion of the silicon-carbon negative electrode material during the lithium insertion process, and the resulting rupture of the electrode material, effectively reducing the consumption of the new SEI film and the electrolyte, and improving the electrochemical performance of the lithium secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the structure of the silicon-carbon composite material containing a covalent organic framework material coating layer of the present invention; Figure 2 This is an electron microscope image of the silicon-carbon composite material before coating; Figure 3 This is an electron microscope image of the silicon-carbon negative electrode material coated with a covalent organic framework material. DETAILED DESCRIPTION
[0035] The present invention will be further described in detail below by way of examples, but the present invention is not limited to the examples. Example
[0036] (1) A silicon-based / porous carbon composite material with a D50 of 7.0 μm, a silicon content of 48.65%, and a specific surface area of 42.3 m2 / g, 2-hydroxy-1,3,5-benzenetricarboxaldehyde (D50 = 16.75 μm) as the first monomer, and 1,3,5-triaminobenzene (D50 = 20.32 μm) as the second monomer were selected as raw materials. The above silicon-based / porous carbon composite material is made of biomass activated carbon (D50 = 6.7 μm, with a specific surface area of 2000 m2). 2 / g, pore volume is 0.72cm 3 / g) was used as raw material, and nitrogen and silane were first introduced into a vertical fluidized bed for silicon deposition (nitrogen flow rate was 10L / min, silane flow rate was 5L / min, deposition temperature was 540°C, and deposition time was 150min). Then, the silane was turned off, the temperature was raised to 640°C, 5L / min of acetylene was introduced, and the temperature was kept at this temperature for 150min.
[0037] (2) The molar ratio of the first monomer to the second monomer is controlled to be 1:1. The coating ratio is 2%, that is, the ratio of the total mass of the first monomer and the second monomer (set as M1) to the mass of the silicon-based / porous carbon composite material (set as M2) (i.e., M1:M2) is 2:100.
[0038] (3) Weigh 30 g of the silicon-based / porous carbon composite material and put it into a 200 ml mixing tank, add 0.3547 g of 2-hydroxy-1,3,5-benzenetricarboxaldehyde, set the planetary mixer (model: MK-PCV-300) to 800 rpm for 5 min, so that the silicon-based / porous carbon composite material and the first monomer are evenly mixed to obtain a primary mixed material, then add 0.2453 g of 1,3,5-triaminobenzene powder to the primary mixed material, and mix again at 800 rpm for 10 min to obtain a secondary mixed material. Heat the secondary mixed material at 150 ° C in a vacuum oven for 12 h to allow it to react fully and remove the moisture generated by the reaction to obtain a cured silicon-carbon composite material containing a covalent organic framework material coating layer.
[0039] (4) The solidified silicon-carbon composite material containing a covalent organic framework material coating layer was placed in a 250 ml beaker, 100 ml of DMF reagent was added, the powder was fully stirred and soaked at room temperature for 10 min, the mixed slurry was divided into 3 50 ml centrifuge tubes, and the solvent was removed by centrifugation in a TG16-WS desktop high-speed centrifuge at a speed of 8000 rpm and a centrifugation time of 5 min. The mixture was washed 3 times in total. After the third wash, the lower precipitate was transferred to a beaker, the mouth of the beaker was covered with dust-free paper, and the mixture was baked in a vacuum oven at 150 °C for 12 h to obtain a purified silicon-carbon composite material containing a covalent organic framework material coating layer.
[0040] The silicon-carbon composite material containing a covalent organic framework material coating layer obtained above comprises a silicon-based / porous carbon composite material and a coating layer coated on the surface of the silicon-based / porous carbon composite material, wherein the coating layer is a covalent organic framework material, and the covalent organic framework material is a crystalline porous polymer material synthesized from a first monomer and a second monomer and connected by covalent bonds; Figure 1 As shown, the above silicon-based / porous carbon composite material is formed by porous carbon 1, silicon particles 2 deposited in the pores of the porous carbon 1 and a carbon film 3 coated on the surface of the porous carbon, and a covalent organic framework material coating layer 4 is coated on the surface of the silicon-based / porous carbon composite material.
[0041] The following equipment was used to characterize the silicon-carbon composite material containing a covalent organic framework material coating layer prepared above.
[0042] The comparative area of the materials was measured using the Quantachrome NOVA 4200e.
[0043] Hitachi scanning electron microscope SU8010 was used to observe the material morphology. The electron microscope image of the silicon-carbon composite material before the covalent organic framework material was coated is shown in the figure. Figure 2 As shown, the electron microscope image of the silicon-carbon composite material containing the covalent organic framework material coating layer of Example 1 is as follows Figure 3 shown.
[0044] The particle size was measured using Bettersize 2600 from Dandong Better Instruments.
[0045] Half-cell performance test: Take 90 parts of the above silicon-carbon composite material containing a covalent organic framework material coating layer, 3 parts of a conductive additive, and 7 parts of a binder, homogenize, coat, dry, and roll in an aqueous system to obtain a silicon-carbon composite material negative electrode sheet containing a covalent organic framework material coating layer. The above silicon-carbon composite material negative electrode sheet containing a covalent organic framework material coating layer is stacked with a diaphragm, a lithium sheet, and a stainless steel gasket in sequence, and 200 μL of electrolyte is added and sealed to form a 2032-type lithium-ion half-cell. The capacity and discharge efficiency are tested using a small (micro) current range device of Wuhan Blue Electric Electronics Co., Ltd.
[0046] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.05μm, and the specific surface area is 1.6㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1737.1mAh / g, the first discharge efficiency of the half-cell is 91.1%, the full charge expansion is 49%, and the retention rate is 87% after 30 cycles. Example
[0047] Compared with Example 1, the difference is that the coating ratio is 0.1%, that is, the mass of 2-hydroxy-1,3,5-benzenetricarboxaldehyde is 0.0177 g, and the mass of 1,3,5-triaminobenzene is 0.0123 g.
[0048] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.01μm, and the specific surface area is 38.5㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1729.3mAh / g, the first discharge efficiency of the half-cell is 90.4%, the full charge expansion is 60%, and the retention rate is 70% after 30 cycles. Example
[0049] Compared with Example 1, the difference is that the coating ratio is 5%, that is, the mass of 2-hydroxy-1,3,5-benzenetricarboxaldehyde is 0.881 g, and the mass of 1,3,5-triaminobenzene is 0.619 g.
[0050] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 8.2μm, and the specific surface area is 1.8㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1685.6mAh / g, the first discharge efficiency of the half-cell is 90%, the full charge expansion is 43%, and the retention rate is 80% after 30 cycles. Example
[0051] Compared with Example 1, the difference is that the coating ratio is 10%, that is, the mass of 2-hydroxy-1,3,5-benzenetricarboxaldehyde is 1.7562 g, and the mass of 1,3,5-triaminobenzene is 1.2438 g.
[0052] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 8.9μm, and the specific surface area is 2.2㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1638.3mAh / g, the first discharge efficiency of the half-cell is 89.7%, the full charge expansion is 42%, and the retention rate is 78% after 30 cycles. Example
[0053] Compared with Example 1, the difference is that the first monomer is 1,4-phenylenediboric acid (D50=24.43um), and the second monomer is 2,4,6-trimethylphenol (D50=32.42um); the molar ratio of the first monomer to the second monomer is 1:2, the mass of the first monomer is 0.227g, and the mass of the second monomer is 0.373g; the heating temperature of the secondary mixture is 120°C, the heating time is 24h, and no purification step is performed.
[0054] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.11μm, and the specific surface area is 3㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1783.8mAh / g, the first discharge efficiency of the half-cell is 92.6%, the full charge expansion is 47%, and the retention rate is 90% after 30 cycles. Example
[0055] Compared with Example 1, the difference is that the first monomer is 3,5-diformylphenylboronic acid (D50=20.27um), and the second monomer is 4,4'-biphenyldiphenol (D50=26.86um); the molar ratio of the first monomer to the second monomer is 1:0.5, the mass of the first monomer is 0.3939g, and the mass of the second monomer is 0.2061g; the heating temperature of the secondary mixture is 150°C, and the heating time is 24h; the solvent used in the purification step is anhydrous ethanol, and the drying temperature after centrifugal washing is 120°C, and the drying time is 12h.
[0056] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.09μm, and the specific surface area is 1.1㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1859.8mAh / g, the first discharge efficiency of the half-cell is 93.9%, the full charge expansion is 46%, and the retention rate is 88% after 30 cycles. Example
[0057] Compared with Example 1, the difference is that the first monomer is 2,2'-biphenyldiboronic acid (D50=37.43um), and the second monomer is 1,4-dialdehyde-2,5-divinylbenzene (D50=49.68um); the mass of the first monomer is 0.339g, and the mass of the second monomer is 0.261g; the heating temperature of the secondary mixture is 180°C, and the heating time is 24h; the solvent used in the purification step is anhydrous ethanol, and the drying temperature after centrifugal washing is 120°C, and the drying time is 12h.
[0058] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.12μm, and the specific surface area is 1.1㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1718.9mAh / g, the first discharge efficiency of the half-cell is 90.6%, the full charge expansion is 53%, and the retention rate after 30 cycles is 82%. Example
[0059] Compared with Example 1, the difference is that a silicon-based / porous carbon composite material with a D50 of 7.50μm, a silicon content of 53.09%, and a specific surface area of 32.4㎡ / g is selected, the first monomer is 2,5-dihydroxyterephthalaldehyde (D50=12.44um), and the second monomer is 2,2'-biphenyldiphenol (D50=41.51um); the mass of the first monomer is 0.2829g, and the mass of the second monomer is 0.3171g; the heating temperature of the secondary mixture is 120°C, and the heating time is 48h. The solvent used in the purification step is anhydrous ethanol, and the drying temperature after centrifugal washing is 120°C, and the drying time is 12h. The silicon-based / porous carbon composite material is based on biomass activated carbon (D50=7.0um, specific surface area of 1950m 2 / g, pore volume is 0.70cm 3 / g) as raw material, in a vertical fluidized bed, nitrogen and silane were first introduced to carry out silicon deposition (nitrogen flow rate was 10L / min, silane flow rate was 5L / min, deposition temperature was 540°C, deposition time was 180min), and then the silane was turned off, the temperature was raised to 640°C, 5L / min of acetylene was introduced and kept warm for 150min to prepare it.
[0060] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.52μm, and the specific surface area is 3㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1962.1mAh / g, the first discharge efficiency of the half-cell is 93.5%, the full-charge expansion is 48%, and the retention rate is 85% after 30 cycles. Example
[0061] Compared with Example 8, the difference is that the first monomer is 2,5-dimethoxyterephthalaldehyde (D50=28.11um), and the second monomer is tetrakis(4-aminophenyl)methane (D50=16.82um); the molar ratio of the first monomer to the second monomer is 1:0.5, the mass of the first monomer is 0.3031g, and the mass of the second monomer is 0.2969g; the heating temperature of the secondary mixture is 180°C, and the heating time is 48h.
[0062] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.56μm, and the specific surface area is 1.7㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 2033.3mAh / g, the first discharge efficiency of the half-cell is 92.8%, the full charge expansion is 42%, and the retention rate is 90% after 30 cycles. Example
[0063] Compared with Example 8, the difference is that the first monomer is 2-formyl-1,4-benzenedicarboxylic acid (D50=44.73um), and the second monomer is 4,5-dimethoxy-1,2-phenylenediamine (D50=42.44um); the mass of the first monomer is 0.2676g, and the mass of the second monomer is 0.3324g; the heating temperature of the secondary mixture is 150°C, and the heating time is 48h.
[0064] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.51μm, and the specific surface area is 2.3㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1959.2mAh / g, the first discharge efficiency of the half-cell is 91.1%, the full charge expansion is 51%, and the retention rate is 87% after 30 cycles. Example
[0065] Compared with Example 8, the difference is that the first monomer is terephthalaldehyde (D50=42.02um), and the second monomer is 1,3,5-tri(4-aminophenyl)benzene (D50=46.7um); the molar ratio of the first monomer to the second monomer is 1:0.67, the mass of the first monomer is 0.2177g, and the mass of the second monomer is 0.3823g; 5ml of acetic acid (purity 99.8%) is added to the secondary mixture as a catalyst, the heating temperature of the secondary mixture is 100°C, and the heating time is 24h.
[0066] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.52μm, and the specific surface area is 2.7㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1927.9mAh / g, the first discharge efficiency of the half-cell is 91.8%, the full charge expansion is 47%, and the retention rate is 86% after 30 cycles. Example
[0067] Compared with Example 8, the difference is that the first monomer is 2,2'-bipyridine-5,5'-dicarboxaldehyde (D50=42.59um), the second monomer is meta-phenylenediamine (D50=16.22um), the molar ratio of the first monomer to the second monomer is 1:2, the mass of the first monomer is 0.2971g, and the mass of the second monomer is 0.3029g; the heating temperature of the secondary mixture is 180°C, and the heating time is 48h; no purification step is performed.
[0068] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.54μm, and the specific surface area is 1.5㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 1948.2mAh / g, the first discharge efficiency of the half-cell is 92.5%, the full charge expansion is 47%, and the retention rate is 88% after 30 cycles. Example
[0069] Compared with Example 8, the difference is that the first monomer is 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (D50=16.38um), the second monomer is 3,4',5-trialdehyde-1,1-biphenyl (D50=20.08um), the molar ratio of the first monomer to the second monomer is 1:2, the mass of the first monomer is 0.2559g, and the mass of the second monomer is 0.3441g; the heating temperature of the secondary mixed material is 200°C, the heating time is 24h, and no purification step is performed, but a carbonization step is added: the secondary mixed material is loaded into a ceramic crucible, and then placed in the middle of a three-temperature zone tubular furnace (Hefei Kejing Material Technology Co., Ltd. OTF-200X-III) for carbonization, the heating rate is 5°C / min, the carbonization temperature is 600°C, the carbonization time is 8h, and the protective gas is nitrogen.
[0070] The test results show that the D50 of the silicon-carbon composite material containing a covalent organic framework material coating layer is 7.53μm, and the specific surface area is 2.6㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared with this material is 2002.1mAh / g, the first discharge efficiency of the half-cell is 93.1%, the full charge expansion is 49%, and the retention rate is 79% after 30 cycles.
[0071] Compared with Example 1, the difference is that the silicon-based / porous carbon composite material is not coated with any organic matter.
[0072] The test results show that the D50 of the silicon-carbon composite material is 7.50μm and the specific surface area is 42.3㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared by this material is 1659.4mAh / g, the first discharge efficiency of the half-cell is 87.6%, the full-charge expansion is 62%, and the retention rate after 30 cycles is 68%.
[0073] Compared with Example 1, the difference is that only the first monomer is added, and the second monomer is not added.
[0074] The test results show that the D50 of the composite material is 7.58μm and the specific surface area is 49.5㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared by this material is 1607.3mAh / g, the first discharge efficiency of the half-cell is 89.2%, the full charge expansion is 65%, and the retention rate after 30 cycles is 70%.
[0075] Compared with Example 1, the difference is that the second monomer is replaced by an equal amount of p-xylene which does not contain active groups such as amino groups, carbonyl groups, boric acid groups or oxazine groups.
[0076] The test results show that the D50 of the composite material is 7.54μm and the specific surface area is 51.8㎡ / g; the first-cycle lithium delithiation capacity of the half-cell prepared by this material is 1598.6mAh / g, the first discharge efficiency of the half-cell is 88.2%, the full charge expansion is 63%, and the retention rate after 30 cycles is 69%.
[0077] It can be seen from the test results of the embodiments and comparative examples that a suitable covalent organic framework material coating layer can significantly reduce the specific surface area of the silicon-based / porous carbon composite material, improve the first discharge efficiency of the half-cell, and reduce the full charge expansion rate of the half-cell. There is an optimal range of the coating ratio of the covalent organic framework material coating layer. When the coating ratio is less than 0.5%, the coating is too little to fully reduce the specific surface area of the silicon-based / porous carbon composite material, and the material performance improvement is limited. When the coating ratio exceeds 10%, the material will agglomerate and the material performance will deteriorate; different types of covalent organic framework material coating layers have different performance improvement effects on the silicon-based / porous carbon composite material.
[0078] The above-mentioned technologies not specifically mentioned are all referred to the prior art.
[0079] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A silicon-carbon composite material containing a covalent organic framework material coating layer, characterized in that: The invention comprises a silicon-based / porous carbon composite material and a coating layer coated on the surface of the silicon-based / porous carbon composite material, wherein the coating layer is a covalent organic framework material, which is a crystalline porous polymer material connected by covalent bonds and synthesized from a first monomer and a second monomer in the presence or absence of a catalyst; the first monomer is one of a boric acid (ester) monomer, a carbonyl monomer, and an oxazine monomer; the second monomer is one of a phenolic monomer, an amino monomer, and a carbonyl monomer.
2. The silicon-carbon composite material containing a covalent organic framework material coating layer according to claim 1, characterized in that: The phenolic monomers are selected from phenolic compounds containing multiple phenolic hydroxyl groups and their aldehyde or amino substituents; the carbonyl monomers are selected from benzaldehyde derivatives and carboxylic acid compounds containing multiple carbonyl groups; the boric acid (ester) monomers are selected from phenylboric acid containing multiple boric acid groups or phenylboric acid substituted with acetylene, formyl, amino, nitro or halogen atoms; the amino monomers are selected from aniline compounds containing multiple amino groups and their derivatives, benzylmethane or aminonaphthalene compounds substituted with multiple aminophenyl groups; the oxazine monomers are selected from polyoxazine compounds, compounds containing multiple pyrimidine rings or compounds containing multiple pyridine rings; the catalyst is a Lewis acid selected from one or more of formic acid, acetic acid, trifluoroacetic acid, benzenesulfonic acid, polyphosphoric acid, benzoic anhydride, acetic anhydride, and toluenesulfonic acid.
3. The method for preparing the silicon-carbon composite material containing a covalent organic framework material coating layer according to claim 1 or 2, characterized in that: The following steps are involved: (1) adding the silicon-based / porous carbon composite material into a mixing tank, adding the first monomer and mixing evenly to obtain a primary mixed material; (2) adding a second monomer to the primary mixed material, and mixing again with or without a catalyst to obtain a secondary mixed material; (3) The secondary mixed material is heated and solidified in a vacuum oven or under the protection of an inert atmosphere to obtain the product.
4. The method for preparing a silicon-carbon composite material containing a covalent organic framework material coating layer according to claim 3, characterized in that: In step (1), the particle size of the silicon-based / porous carbon composite material is 0.1-80 μm, the mass percentage of silicon is 20%-80%, and the BET multi-point specific surface area is 0.1-500 m2 / g.
5. The method for preparing a silicon-carbon composite material containing a covalent organic framework material coating layer according to claim 3, characterized in that: In step (1)-step (2), the particle size of the first monomer is 0.1-200 μm, and the particle size of the second monomer is 0.1-200 μm; the molar ratio of the first monomer to the second monomer is 1:0.2-6; and the ratio of the total mass of the first monomer and the second monomer to the mass of the silicon-based / porous carbon composite material is 0.05%-20%.
6. The method for preparing a silicon-carbon composite material containing a covalent organic framework material coating layer according to claim 3, characterized in that: In step (1), the mixing speed of the primary mixed material is 200-3000 rpm, and the mixing time is 5-180 min; in step (2), the mixing speed of the secondary mixed material is 200-3000 rpm, and the mixing time is 5-180 min; in step (3), the heating temperature during heating and curing is 60°C-400°C, and the heating time is 0.5-168h.
7. The method for preparing a silicon-carbon composite material containing a covalent organic framework material coating layer according to any one of claims 3 to 6, characterized in that: The method further comprises step (4) after step (3): under the protection of an inert gas, heating the silicon-carbon composite material containing the covalent organic framework material coating layer from room temperature to a carbonization temperature, keeping the temperature for a certain period of time, and then cooling the temperature to obtain a carbonized silicon-carbon composite material containing the covalent organic framework material coating layer.
8. The method for preparing a silicon-carbon composite material containing a covalent organic framework material coating layer according to claim 7, characterized in that: In step (4), the inert gas is nitrogen or argon, the heating rate is 0.1-50°C / min, the carbonization temperature is 500-1000°C, and the carbonization time is 1-12h.
9. The method for preparing a silicon-carbon composite material containing a covalent organic framework material coating layer according to claim 7 or 8, characterized in that: A purification step is also included between step (3) and step (4): adding a sufficient amount of organic solvent to the silicon-carbon composite material containing the covalent organic framework material coating layer, fully stirring, removing the solvent after soaking for a period of time, and drying the powder to obtain a purified silicon-carbon composite material containing the covalent organic framework material coating layer.
10. The method for preparing a silicon-carbon composite material containing a covalent organic framework material coating layer according to claim 9, characterized in that: In the purification step, the organic solvent is selected from one or more of ethanol, isopropanol, dimethylformamide, pentane, hexane, octane, methyl acetate, ethyl acetate, propyl acetate, and acetone; the method for removing the solvent includes precipitation, centrifugation, and filtration, and the drying is carried out under vacuum or inert atmosphere, the drying temperature is 60-300°C, and the drying time is 0.5-12h.
Citation Information
Cited By
Negative electrode material and preparation method and application thereof
CN121035191A